Informal talks about writing as a constructive way to develop young L2 learner print awareness - Zawodniak, Joanna (Glottodidactica, 2011)
The article examines the possibilities of fostering young L2 learner print awareness via teaching for conversing about and reflecting on writing. In order to achieve this goal the present author conducted the qualitative research on a group of 2nd-graders engaged in the performance of a series of open-ended L2 written tasks accompanied by L1 cues. The analysis of collected data shows that drawing children’s conscious attention to writing might encourage the constructive transferability of linguistic skills from L1 to L2, thus being conducive to the development of logical thinking necessary for the enhancement of their print awareness.